2004
DOI: 10.1051/0004-6361:20041047
|View full text |Cite
|
Sign up to set email alerts
|

The photospheric abundances of active binaries

Abstract: Abstract. We report the determination from high-resolution spectra of the atmospheric parameters and abundances of 13 chemical species (among which lithium) in 8 single-lined active binaries. These data are combined with our previous results for 6 other RS CVn systems to examine a possible relationship between the photospheric abundance patterns and the stellar activity level. The stars analyzed are generally found to exhibit peculiar abundance ratios compared to inactive, Galactic disk stars of similar metall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 54 publications
8
31
0
Order By: Relevance
“…From the mean abundances of our reference stars (Taylor 1999), we estimate an [Fe/ H] value that is slightly less than solar. This is in reasonable agreement with determinations by Fekel & Balachandran (1994), Morel et al (2004), and Randich et al (1993), who found ½Fe=H ¼ 0:0, À0.09, and À0.3, respectively.…”
Section: Spectral Type and Abundancesupporting
confidence: 93%
See 1 more Smart Citation
“…From the mean abundances of our reference stars (Taylor 1999), we estimate an [Fe/ H] value that is slightly less than solar. This is in reasonable agreement with determinations by Fekel & Balachandran (1994), Morel et al (2004), and Randich et al (1993), who found ½Fe=H ¼ 0:0, À0.09, and À0.3, respectively.…”
Section: Spectral Type and Abundancesupporting
confidence: 93%
“…Thus, we classify it as a K0 III and conclude that its [Fe/ H] abundance is essentially solar. Our spectral type is in agreement with that given by Bidelman (1981) and Houk & Swift (1999), while our estimated iron abundance is in accord with ½Fe=H ¼ 0:0 found by Fekel & Balachandran (1994) and ½Fe=H ¼ À0:16 determined by Morel et al (2004).…”
Section: Spectral Type and Abundancesupporting
confidence: 93%
“…Further details can be found in Morel et al (2003Morel et al ( , 2004. As discussed in these papers, the selected transitions of the odd-Z elements (Sc, Co, and Ba) are not significantly broadened by hyperfine structure.…”
Section: Curve-of-growth Analysismentioning
confidence: 91%
“…Moreover, as the star becomes cooler, the line blending becomes stronger, causing a possible [Fe/H] underestimation. An extensive study of the influence of stellar spots on deriving stellar parameters can be found, for instance, in Morel et al (2004). A possible influence of the atmospheric models used, optimal in the temperature window considered, cannot be discarded.…”
Section: [Fe/h] Correctionmentioning
confidence: 99%